Predictions of electricity prices as embedded devices for coordinating European futures - Aleksandra Lis-Plesińska (economic sociology. perspectives and conversations, 2022)
With the completion of mass electrification projects in Europe, electricity supply seemed to have gradually escaped the political attention of European publics. No more new villages to connect to the national power grid, no more political celebrations of remote communities entering modernity and sharing its achievements. Electricity supply, even if randomly exposed to delivery cuts, became a taken-for-granted good, an invisible, though acutely essential, part of modern economic infrastructure.
Keywords: 300